THE PREVALENCE OF PRE-DIABETES AND DIABETES AMONG OVERWEIGHT AND OBESE PATIENTS IN A SINGLE-CENTRE - Bahrudin, Mohd Fyzal; Ng, Ooi Chuan (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Overweight and obesity increase the risk of diabetes mellitus, and 84% of Malaysians with Type 2 Diabetes Mellitus (T2DM) are obese. While the local prevalence of prediabetes and diabetes are 11.62% and 18.3% respectively, there is paucity of data on its prevalence among those who are overweight and obese. METHODOLOGY This is a cross-sectional cohort study among participants of the Weight Loss Journey Program in Hospital Sultan Abdul Aziz Shah, University Putra Malaysia in March 2023. Overweight is defined as BMI ≥23.0 kg/m² and obese is defined as BMI ≥27.5 kg/m². Participants who agreed to do baseline blood exams were investigated for prediabetes and diabetes by measuring their baseline fasting blood glucose (FBS) and HbA1c. RESULT There were 151 participants in the weight loss challenge. The mean age was 33 years old and majority were female (n=124). Mean weight was 80.9 kg (51.1 – 158.1 kg) with mean BMI of 31.6 kg/m² (23.0- 57.5 kg/m²). Six patients were excluded as they were known to have DM. A total of 68 participants agreed to undergo screening for diabetes by measuring FBS and HbA1c. The mean FBS and HbA1c were 4.66 mmol/L (3.8- 5.9 mmol/L) and 5.5% (4.5-6.5%), respectively. Interestingly, 39.7% (27 out of 68 subjects) had prediabetes, and only 6% (4 out of 68 subjects) met the criteria for diabetes. Conclusion Higher than normal BMI appear to pose a 3.3-fold increased risk of prediabetes compared to the general population. This is worrying given their relatively young age and only moderately high BMI levels. Nevertheless, the noted small proportion of undiagnosed DM in this patient population may reflect recent improvements in screening and detection of DM.